Biological nitrogen fixation and urea-N recovery in 'Coastcross-1' pasture treated with Azospirillum brasilense - Aguirre, Priscila Flôres; Giacomini, Sandro José; Olivo, Clair Jorge; Bratz, Vinicius Felipe; Quatrin, Maurício Pase; Schaefer, Gilmar Luiz (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to quantify the inoculation effect of Azospirillum brasilense (Ab-V5 and Ab-V6 strains) on the forage yield, biological nitrogen fixation (BNF), and urea-15N recovery of the forage grass 'Coastcross-1'. The experiment was carried out in a 2 (with or without inoculation) × 2 (without N fertilizer and with 100 kg ha-1 N per year as urea) × 7 (cuts) factorial arrangement. The natural 15N abundance method was used to determine BNF; to determine urea-N recovery, 15N-labeled urea was applied in microplots. Forage yield was higher in grasses subjected to inoculation, with 7.4 Mg ha-1 dry matter per year, for the treatment without N fertilizer, and 8.0 Mg ha-1 dry matter per year for the treatment with 100 kg ha-1 N per year, respectively, which shows an additive effect of inoculation and N fertilization. The contribution of BNF was 23.0 and 53.8 kg ha-1 per year for the unfertilized treatment, both in uninoculated and inoculated plants, respectively. Urea-15N recovery was 13.7 and 16.5 kg ha-1 per year for uninoculated and inoculated treatments, respectively, corresponding to 13.7 and 16.5% of the urea-N applied. Inoculation with A. brasilense increases forage yield and the contribution of BNF to grass nutrition with N, as well as urea-N recovery by the forage grass.